Shearing-resistant high-drag-reduction medium-viscosity slickwater drag reducer and preparation method thereof
Through the polymerization reaction of acrylamide and sulfonate-containing ionic hydrophobic monomers, a shear-resistant high-resistance medium-slimy-water-reducing drag-reducing agent is formed, and polyacrylamide in the deep/ultra-deep oil and gas reservoirs in the prior art is solved. The problems of degraded drag reduction performance and poor sand carrying performance have achieved efficient deep/ultra-deep oil and gas resource development.
Patent Information
- Application Number
- CN202411437864.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The existing high molecular weight polyacrylamide is difficult to meet the requirements of high drag reduction and sand carrying during the volume fracturing process of deep/ultra-deep oil and gas reservoirs, and is easily degraded under high displacement conditions, resulting in a decrease in drag reduction performance and a weakening of sand carrying performance. .
Polymerization reaction is carried out using acrylamide, sulfonate-containing ionic hydrophobic monomer, hydrophobic unit microblock regulator, molecular weight grader and composite initiator to form a shear-resistant high resistance to reduce medium viscosity and slippery water resistance reduction agent, through control The molecular structure and reaction conditions of the polymer improve the resistance to shear degradation and sand carrying properties.
The shear degradation and sand carrying properties of the drag reducer are significantly improved, meeting the requirements of deep/ultra-deep oil and gas reservoirs for high drag reduction and sand carrying, and ensuring the efficient development of deep/ultra-deep oil and gas resources.
Smart Images

Figure CN119241766A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of deep well / ultra-deep well volume fracturing, and in particular to a shear-resistant, high-drag-reducing, medium-viscosity slick water drag reducer and a preparation method thereof. Background Art
[0002] In the process of volume fracturing of unconventional oil and gas reservoirs, in order to form a complex sealing network and effectively support the complex sealing network, medium-viscosity slick water (5-10mPa.s) is used in large quantities, and the medium-viscosity slick water is required to have high drag reduction and high sand carrying capacity. Therefore, high molecular weight polyacrylamide is increasingly used, and the molecular weight of some polyacrylamide reaches more than 30 million. However, under high displacement conditions, the Reynolds number is large, the turbulence is severe, and the Reynolds shear degradation is obvious. The higher the molecular weight, the more severe the degradation. On the one hand, the degradation of molecular weight leads to a decrease in drag reduction performance, and on the other hand, the loss of viscoelasticity leads to a weakening of sand carrying performance. In addition to large displacement, the volume fracturing of deep / ultra-deep oil and gas reservoirs is also accompanied by the challenge of long wellbore, which makes the degradation more obvious and puts forward higher requirements for the shear resistance of the drag reducer. Existing linear high molecular weight polyacrylamide is difficult to meet the requirements of "high wellbore drag reduction and long sand carrying capacity" for fracturing of deep / ultra-deep oil and gas reservoirs. This technical bottleneck has posed a significant obstacle to the development of deep and ultra-deep oil and gas resources. Therefore, it is urgent to develop a medium-viscosity slick water drag reducer with shear resistance, high drag reduction and high sand carrying capacity. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a shear-resistant, high-drag-reducing, medium-viscosity slippery water drag reducer and a preparation method thereof. The drag reducer is formed by polymerization of acrylamide, a sulfonate ion-containing hydrophobic monomer, a hydrophobic unit microblock regulator, a molecular weight grading agent and a composite initiator. The present invention can significantly improve the polymer solubility and viscosity-increasing properties through the control of a special sulfonate ion-containing hydrophobic monomer, a hydrophobic unit microblock regulator matched with the hydrophobic monomer and the molecular weight of the polymer; improve the shear degradation resistance of the drag reducer; have excellent sand carrying performance and drag reduction performance; overcome the shortcomings of the existing drag reducers such as weak shear resistance, fast drag reduction rate drop, and poor sand carrying performance, and can meet the special requirements of deep / ultra-deep oil and gas reservoir fracturing on fracturing fluid rheology and "high wellbore drag reduction". The invention provides key material support for the development of deep / ultra-deep oil and gas resources and ensures the goal of efficient development of deep / ultra-deep oil and gas resources.
[0004] In order to achieve the above technical effects, the following technical solutions are adopted: A shear-resistant, high-drag-reducing, medium-viscosity, slippery water drag reducer, prepared by polymerization of acrylamide, a sulfonate-containing ion-type hydrophobic monomer, a hydrophobic unit microblock regulator, a molecular weight regulator, and a composite initiator; The molecular structure of the drag reducer is: ; Wherein, x, y, z are the number of each repeating unit; The molar ratio of acrylamide to sulfonate ion-containing hydrophobic monomer is 1: 0.001-0.003; The mass ratio of the hydrophobic unit microblock regulator to the sulfonate ion-containing hydrophobic monomer is 6:1-4:1; The mass ratio of molecular weight regulator to reaction system is 0.0025%-0.0075%; The mass ratio of the composite initiator to the reaction system is 0.0115%-0.0225%; After the polymerization reaction is completed, sodium hydroxide is used for post-hydrolysis, and the molar ratio of acrylamide monomer to sodium hydroxide is 1:0.2-0.4; The structural formula of the sulfonate ion-containing hydrophobic monomer is: ; Wherein, the R group is a C14 alkyl group or a C16 alkyl group; The hydrophobic unit microblock regulator is one or more of AEO-7 and AEO-9; The molecular weight regulator is one or more of sodium formate, sodium hypophosphite, and n-butyl mercaptan; The composite initiator is a multi-element initiator, which is composed of an inorganic oxidant, an organic oxidant, a reducing agent, and a water-soluble azo initiator. The inorganic oxidant is a persulfate, and the addition amount is 0.002-0.004% of the reaction system; the organic oxidant is an organic hydrogen peroxide, and the addition amount is 0.001-0.003% of the reaction system; the reducing agent is a sulfite and a bisulfite, and the addition amount is 0.0075-0.0125% of the reaction system; the addition amount of the water-soluble azo initiator is 0.001-0.003% of the reaction system.
[0005] Furthermore, the molecular weight of the drag reducer is in the range of 25-30 million.
[0006] Furthermore, the inorganic oxidant is ammonium persulfate, sodium persulfate, potassium persulfate, or hydrogen peroxide; and the organic oxidant is one or more of tert-butyl hydroperoxide and cumene hydroperoxide.
[0007] Furthermore, the reducing agent is one of sodium sulfite, sodium bisulfite and sodium metabisulfite.
[0008] Furthermore, the water-soluble azo initiator is one of 2,2-azo(2-(2-imidazolin-2-yl)propane) dihydrochloride, 2,2-azo(2-methyl-N-(2-hydroxyethyl)acrylamide), and 2,2-azobis(2-methylpropane) hydrochloride.
[0009] Furthermore, the composite initiator is tert-butyl hydroperoxide, ammonium persulfate, sodium bisulfite, and 2,2-azo(2-(2-imidazoline-2-yl)propane) dihydrochloride.
[0010] Furthermore, the preparation method of the sulfonate ion-containing hydrophobic monomer is: Step S1: In a three-necked flask equipped with a magnetic stirrer, a reflux cold flow tube, a thermometer, and two constant pressure dropping funnels, tetradecylamine or hexadecylamine and a catalyst are added in sequence, 2-sodium bromoethylsulfonate or 2-sodium chloroethylsulfonate solution is added to one of the constant pressure funnels, and NaOH solution is added to the other constant pressure dropping funnel; the reaction pH is controlled to be weakly alkaline (9-12), and the reaction is carried out at a temperature of 50-70° C. for 6-9 hours; after the reaction is completed, a precipitate is precipitated in ethanol, and filtered to obtain an intermediate sodium 2-tetradecylaminoethanesulfonate or sodium 2-hexadecylaminoethanesulfonate; Step S2: dissolving the intermediate obtained in step S1 in dichloromethane, and adding Na2CO3 as an acid binding agent; dropping acryloyl chloride from a constant pressure dropping funnel, controlling the temperature at 15-20°C, reacting for 18-24 hours, removing dichloromethane by reduced pressure distillation, and then recrystallizing with ethanol to obtain the target monomer, which is a sulfonate ion-containing hydrophobic monomer.
[0011] Furthermore, in the step S1, the molar ratio of tetradecylamine or hexadecylamine to sodium 2-bromoethylsulfonate or sodium 2-chloroethylsulfonate is 1:0.8-1:0.9; the catalyst is tetrabutylammonium bromide, and its content is 1% of the mass of tetradecylamine or hexadecylamine; during the reaction, the dropping speed of the NaOH solution is adjusted according to the pH change to control the pH at 9-12; in the step S2, the molar ratio of the intermediate, Na2CO3, and acryloyl chloride is 1:3:3.
[0012] A method for preparing a shear-resistant, high-drag-reducing medium-viscosity slippery water drag reducer, which is a post-hydrolysis process: The acrylamide monomer and the sulfonate ion-containing hydrophobic monomer are added according to the formula ratio, and ultrapure water is used to prepare a mixed solution with a total monomer mass concentration of 20-35%; the hydrophobic unit microblock regulator and the molecular weight regulator are added to the mixed solution, and then the pH value of the solution is adjusted to 7.0-9.0, and the system temperature is lowered to 0-5°C and then a water-soluble azo initiator and a reducing agent are added; nitrogen is introduced and stirred for 30-40 minutes, and then an oxidant is added, and adiabatic polymerization is carried out for 3-8 hours. After the adiabatic polymerization is completed, granulation, hydrolysis, drying, and crushing are carried out to obtain a target polymer.
[0013] Furthermore, the pH value of the solution is adjusted by sodium hydroxide and acetic acid; the pH value of the solution is 8.0-8.5; the system temperature is 0° C.; and the insulating polymer time is 5-7 hours.
[0014] The invention discloses a shear-resistant high-drag-reducing medium-viscosity slippery water drag reducer and a preparation method thereof. The drag reducer is prepared by polymerization reaction of acrylamide, a sulfonate ion-containing hydrophobic monomer, a hydrophobic unit microblock regulator, a molecular weight regulator and a composite initiator. The invention cooperates with each other through the special sulfonate ion-containing hydrophobic monomer, the hydrophobic unit microblock regulator matched with the hydrophobic monomer and the control of the polymer molecular weight, and synergistic polymerization is achieved. The several polymer substances act together to synthesize a polymer molecular structure that is different from the prior art. The difference in molecular structure and the superiority of the molecular structure can significantly improve the polymer solubility and viscosity-increasing performance; improve the shear degradation resistance of the drag reducer; have excellent sand carrying performance and drag reduction performance; overcome the shortcomings of the existing drag reducer such as weak shear resistance, fast drag reduction rate drop, and poor sand carrying performance, and can meet the special requirements of deep / ultra-deep oil and gas reservoir fracturing on fracturing fluid rheology and "high wellbore drag reduction". The invention provides key material support for the development of deep / ultra-deep oil and gas resources and ensures the goal of efficient development of deep / ultra-deep oil and gas resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. The drawings in the following description are merely embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.
[0016] Figure 1 is the H of the sulfonate ion type hydrophobic monomer in the embodiment of the present invention. 1 - NMR spectra; Figure 2 It is the HPLC-MS chart of the sulfonate ion type hydrophobic monomer in the embodiment of the present invention. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0018] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0019] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations and / or combinations thereof.
[0020] First, a sulfonate ion-containing hydrophobic monomer is synthesized, and the preparation method thereof is as follows: Step S1: In a three-necked flask equipped with a magnetic stirrer, a reflux cold flow tube, a thermometer, and two constant pressure dropping funnels, tetradecylamine or hexadecylamine and a catalyst (tetrabutylammonium bromide) are added in sequence, 2-bromoethyl sodium sulfonate or 2-chloroethyl sodium sulfonate solution is added to one of the constant pressure funnels, and NaOH solution is added to the other constant pressure dropping funnel; the pH value of the reaction is controlled by adjusting the dropping speed of the NaOH solution, and the reaction is carried out at a temperature of 50-70° C. for 6-9 hours; after the reaction is completed, a precipitate is precipitated in ethanol, and filtered to obtain an intermediate sodium 2-tetradecylaminoethanesulfonate or sodium 2-hexadecylaminoethanesulfonate; In the step S1, the molar ratio of tetradecylamine or hexadecylamine to sodium 2-bromoethylsulfonate or sodium 2-chloroethylsulfonate solution is 1:0.8-1:0.9; the catalyst is tetrabutylammonium bromide, and its content is 1% of the mass of tetradecylamine or hexadecylamine; and the pH value is controlled between 9 and 12 by controlling the dripping speed of the sodium hydroxide solution.
[0021] Step S2: dissolving the intermediate obtained in step S1 in dichloromethane, and adding Na2CO3 as an acid binding agent; dropping acryloyl chloride from a constant pressure dropping funnel, controlling the temperature at 20°C, reacting for 18 hours, removing dichloromethane by reduced pressure distillation, and then recrystallizing with ethanol to obtain the target monomer, which is a sulfonate ion-containing hydrophobic monomer (R group is a C16 or C14 alkyl group); in step S2, the molar ratio of the intermediate, Na2CO3, and acryloyl chloride is 1:3:3.
[0022] The obtained H containing sulfonate ion type hydrophobic monomer (R group is C14 alkyl) 1 -NMR images Figure 1 As shown; the HPLC-MS diagram of the hydrophobic monomer containing sulfonate ions (R group is C14 alkyl) is as follows Figure 2 shown.
[0023] Example 1
[0024] The acrylamide monomer and the sulfonate ion-containing hydrophobic monomer (R group is a C16 alkyl) were added in a ratio of 1:0.002, and ultrapure water was used to prepare a mixed solution with a total monomer mass concentration of 25%; the hydrophobic unit microblock regulator AEO-7 was added to the mixed solution, and the addition amount was a hydrophobic unit microblock regulator and hydrophobic monomer mass ratio of 5:1, and 50ppm of sodium formate, a molecular weight regulator, was added, and then the pH value of the solution was adjusted to 8.0 using sodium hydroxide and acetic acid, and the system was stirred for 2 hours. After the temperature is adjusted to 0°C, 100 ppm of sodium bisulfite, 30 ppm of ammonium persulfate, and 10 ppm of azo initiator 2,2-azo (2- (2-imidazoline-2-yl) propane) dihydrochloride are added, nitrogen is introduced and stirred for 30 minutes, and then 20 ppm of tert-butyl hydroperoxide is added, and adiabatic polymerization is performed for 3-8 hours. After the adiabatic polymerization is completed, granulation, hydrolysis (adding sodium hydroxide with a molar mass of 30% of acrylamide, sealed and hydrolyzed at 90°C for 2 hours), drying, and crushing are performed to obtain the target polymer. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Example 1 is tested and calculated according to GB / T 12005.10-92 using an Ubbelohde viscometer (0.55 mm diameter) to be 27 million.
[0025] Example 2
[0026] The method of Example 1 was followed, except that the amount of sodium hydroxide added during hydrolysis was 20% of the molar mass of acrylamide. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Example 2 was measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92, and was 26.4 million.
[0027] Example 3
[0028] The method of Example 1 was followed, except that the amount of sodium hydroxide added during hydrolysis was 40% of the molar mass of acrylamide. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Example 3 was measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92, and was 26.5 million.
[0029] Example 4
[0030] The method of Example 1 was followed, except that the acrylamide monomer and the sulfonate ion-containing hydrophobic monomer were added in a ratio of 1:0.003. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Example 4 was measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92 and was 26.7 million.
[0031] Example 5
[0032] The method of Example 1 was followed, except that the acrylamide monomer and the sulfonate ion-containing hydrophobic monomer were added in a ratio of 1:0.001. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Example 5 was measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92 and was 27.1 million.
[0033] Example 6
[0034] The method of Example 1 was followed, except that the mass ratio of the hydrophobic unit microblock regulator to the hydrophobic monomer was 6: 1. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Example 6 was measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92, and was 26.2 million.
[0035] Example 7
[0036] The method of Example 1 was followed, except that the mass ratio of the hydrophobic unit microblock regulator to the hydrophobic monomer was 4: 1. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Example 7 was measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92, and the result was 26.8 million.
[0037] Example 8
[0038] The method of Example 1 was followed, except that the hydrophobic unit microblock regulator was replaced with AEO-9. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Example 8 was measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92, and was 27.1 million.
[0039] Comparative Example 1 The method of Example 1 was followed, except that the R group of the sulfonate ion hydrophobic monomer was a C12 alkyl group. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 1 was 27.4 million, as measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92.
[0040] Comparative Example 2 The method of Example 1 was followed, except that the R group of the sulfonate ion hydrophobic monomer was a C18 alkyl group. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 2 was 26.9 million, as measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92.
[0041] Comparative Example 3 The method of Example 1 was followed, except that the hydrophobic monomer was dimethyl hexadecyl allyl ammonium chloride. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 3 was 27.2 million, as measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92.
[0042] Comparative Example 4 The method of Example 1 was followed, except that the mass ratio of the hydrophobic unit microblock regulator to the hydrophobic monomer was 7: 1. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 4 was tested and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92, and the result was 27.3 million.
[0043] Comparative Example 5 The method of Example 1 was followed, except that the mass ratio of the hydrophobic unit microblock regulator to the hydrophobic monomer was 3: 1. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 5 was 27.5 million, as measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92.
[0044] Comparative Example 6 The method of Example 1 was followed, except that the amount of the molecular weight modifier sodium formate was increased to 100 ppm. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 6 was tested and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92 to be 20 million.
[0045] Comparative Example 7 The method of Example 1 was followed, except that the amount of sodium formate added as the molecular weight regulator was reduced to 10 ppm. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 7 was 33 million, as measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92.
[0046] Comparative Example 8 The method of Example 1 was followed, except that the hydrophobic unit microblock regulator was replaced with AEO-5. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 8 was 27.2 million, as measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92.
[0047] Comparative Example 9 The method of Example 1 was followed, except that the hydrophobic unit microblock regulator was replaced with AEO-15. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 9 was 27.1 million, as measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92.
[0048] Comparative Example 10 The method of Example 1 was followed, except that the hydrophobic unit microblock regulator was replaced with OP-10. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 10 was 27.3 million, as measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92.
[0049] Comparative Example 11 The difference from Example 1 is that: a copolymerization process is used to introduce sodium acrylate fragments. The specific route is as follows: acrylamide monomer, sodium acrylate monomer, and sulfonate ion-containing hydrophobic monomer (R group is a C16 alkyl) are added in a ratio of 1:0.3:0.002, and ultrapure water is used to prepare a mixed solution with a total monomer mass concentration of 25%; a hydrophobic unit microblock regulator AEO-7 is added to the mixed solution in an amount such that the mass ratio of the microblock regulator to the hydrophobic monomer is 5:1, and a molecular weight of 1000 mol / L is added. 50ppm of sodium formate as a grading agent was added, and then sodium hydroxide and acetic acid were used to adjust the solution pH to 8.0. After the system temperature was adjusted to 0°C, 100ppm of sodium bisulfite, 30ppm of ammonium persulfate, and 10ppm of azo initiator 2,2-azo (2- (2-imidazoline-2-yl) propane) dihydrochloride were added. After nitrogen was introduced and stirred for 30 minutes, 20ppm of tert-butyl hydroperoxide was added, and adiabatic polymerization was performed for 3-8h. After the adiabatic polymerization was completed, granulation, drying, and crushing were performed to obtain the target polymer. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 11 was tested and calculated according to GB / T12005.10-92 using an Ubbelohde viscometer (0.55mm diameter) to be 20 million.
[0050] Comparative Example 12 The method of Example 1 was followed, except that no hydrophobic unit microblock regulator was added. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Example 2 was measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92, and the result was 27.2 million.
[0051] Comparative Example 13 The method of Example 1 was followed, except that no azo component was added to the initiator. The reaction failed, the colloid was very soft, and a large amount of unpolymerized liquid was present.
[0052] Comparative Example 14 The method of Example 1 was followed, except that ammonium persulfate was not added to the initiator. The reaction failed, and the temperature was not raised further after the reaction temperature reached 20°C, and a large amount of monomers were not polymerized, resulting in the reaction failure.
[0053] Comparative Example 15 The method of Example 1 was followed, except that tert-butyl hydroperoxide was not added to the initiator. The reaction could not be initiated and the polymerization failed.
[0054] Comparative Example 16 The mainstream high molecular weight drag reducer on the market is partially hydrolyzed polyacrylamide, with a molecular weight of 30 million and a degree of hydrolysis of 30%.
[0055] The performance evaluation method of the polymer solution in the embodiments and comparative examples is as follows: (1) Adhesion time test 400 mL of clean water was added to 1000 mL beakers respectively. At a stirring speed of 500 r / min, 0.04% of the sample was added respectively. The viscosity-increasing time (glass rod can be drawn) after adding the thickener was recorded. The specific data are shown in Table 1.
[0056] (2) Viscosity test Stir in clean water at 25°C and 500 r / min for 3 min and measure with a six-speed viscometer for 170 s -1 The viscosity of each sample was 0.04%, 0.05%, 0.06% and 0.07% respectively. The results are shown in Table 1. Then, the concentrations corresponding to the viscosities of 5 mPa·s and 10 mPa·s of each sample were found through fitting and concentration adjustment. The results are shown in Table 2.
[0057] Table 1 Sample tack time and tackifying properties
[0059] Comparative polymers that failed to meet the standards in the tack build test and tack time test were not evaluated for other properties.
[0060] Table 2 Concentrations corresponding to sample viscosities of 5mPa·s and 10mPa·s
[0061] (3) Drag reduction performance The drag reduction rates of the test examples and comparative examples were measured in accordance with the provisions of Chapter 7.8 of SY-T 7627-2021 for determining the drag reduction rate, and the 5-min drag reduction rate data was taken as the drag reduction rate value, as shown in Table 3.
[0062] Table 3 Drag reduction rate corresponding to sample viscosity of 5mPa·s and 10mPa·s
[0063] (4) Sand carrying performance Take 1000 mL of the target solution and prepare about 400 mL. Stir at 500 r / min for 3 min during sample preparation. Pour 100 mL of the test solution into a 100 mL measuring cylinder, and then test the sedimentation rate of 20 / 40 mesh ceramsite in the measuring cylinder. Repeat the test of the sedimentation rate of 20 ceramsite particles, and then take the average value, as shown in Table 4.
[0064] Table 4 Sedimentation velocity corresponding to sample viscosity of 5mPa·s and 10mPa·s
[0065] (5) Shear resistance Prepare about 400 mL of the target solution in a 1000 mL beaker. Stir at 500 r / min for 3 min. Take 300 mL of the test solution and measure it for 170 s using a six-speed rotational viscometer. -1 The viscosity value (mP a·s) was measured. After the test, the mixture was poured into a WARING mixer and sheared at a speed of 3000 r / min for 5 min before and after shearing. The viscosity retention values before and after shearing were calculated, as shown in Table 5.
[0066] Table 5 Viscosity shear retention rate corresponding to sample viscosity of 5mPa·s and 10mPa·s
[0067] In summary, the present invention discloses a shear-resistant high-drag-reducing medium-viscosity slippery water drag reducer and a preparation method thereof. The drag reducer is formed by polymerization reaction of acrylamide, a sulfonate ion-containing hydrophobic monomer, a hydrophobic unit microblock regulator, a molecular weight regulator and a composite initiator. The present invention cooperates with each other through the special sulfonate ion-containing hydrophobic monomer, the hydrophobic unit microblock regulator matched with the hydrophobic monomer and the control of the polymer molecular weight, and synergistic polymerization. Several polymer substances work together to synthesize a polymer molecular structure that is different from the prior art. The difference in molecular structure and the excellence of the molecular structure can significantly improve the polymer solubility and viscosity-increasing performance; improve the shear degradation resistance of the drag reducer; have excellent sand carrying performance and drag reduction performance; overcome the shortcomings of the existing drag reducers such as weak shear resistance, fast decline in drag reduction rate, and poor sand carrying performance, and can meet the special requirements of deep / ultra-deep oil and gas reservoir fracturing on fracturing fluid rheology and "high wellbore drag reduction". The invention provides key material support for the development of deep / ultra-deep oil and gas resources and ensures the goal of efficient development of deep / ultra-deep oil and gas resources.
[0068] At this point, those skilled in the art recognize that, although the embodiments of the present invention have been shown and described in detail herein, many other variations or modifications that conform to the principles of the present invention can still be directly determined or derived based on the contents disclosed in the present invention without departing from the spirit and scope of the present invention. Therefore, the scope of the present invention should be understood and recognized as covering all such other variations or modifications.
Claims
1. A shear-resistant, high-drag-reducing, medium-viscosity, slippery water drag reducer, characterized in that: The drag reducer is formed by polymerization reaction of acrylamide, sulfonate ion-containing hydrophobic monomer, hydrophobic unit microblock regulator, molecular weight regulator and composite initiator; The molecular structure of the drag reducer is: ; Wherein, x, y, z are the number of each repeating unit; The molar ratio of acrylamide to sulfonate ion-containing hydrophobic monomer is 1: 0.001-0.003; The mass ratio of the hydrophobic unit microblock regulator to the sulfonate ion-containing hydrophobic monomer is 6:1-4:1; The mass ratio of molecular weight regulator to reaction system is 0.0025%-0.0075%; The mass ratio of the composite initiator to the reaction system is 0.0115%-0.0225%; After the polymerization reaction is completed, sodium hydroxide is used for post-hydrolysis, and the molar ratio of acrylamide monomer to sodium hydroxide is 1:0.2-0.4; The structural formula of the sulfonate ion-containing hydrophobic monomer is: ; Wherein, the R group is a C14 alkyl group or a C16 alkyl group; The hydrophobic unit microblock regulator is one or more of AEO-7 and AEO-9; The molecular weight regulator is one or more of sodium formate, sodium hypophosphite, and n-butyl mercaptan; The composite initiator is a multi-element initiator, which is composed of an inorganic oxidant, an organic oxidant, a reducing agent, and a water-soluble azo initiator. The oxidant is an inorganic persulfate, and the addition amount is 0.002-0.004% of the reaction system; the organic oxidant is an organic hydrogen peroxide, and the addition amount is 0.001-0.003% of the reaction system; the reducing agent is a sulfite and a bisulfite, and the addition amount is 0.0075-0.0125% of the reaction system; the addition amount of the water-soluble azo initiator is 0.001-0.003% of the reaction system.
2. A shear-resistant, high-drag-reducing, medium-viscosity, slippery water drag reducer as claimed in claim 1, characterized in that: The molecular weight of the drag reducer is in the range of 25-30 million.
3. A shear-resistant, high-drag-reducing, medium-viscosity, slippery water drag reducer as claimed in claim 1, characterized in that: The inorganic oxidant is ammonium persulfate, sodium persulfate, potassium persulfate, or hydrogen peroxide; the organic oxidant is one or more of tert-butyl hydroperoxide and cumene hydroperoxide.
4. A shear-resistant, high-drag-reducing, medium-viscosity, slippery water drag reducer as claimed in claim 1, characterized in that: The reducing agent is one of sodium sulfite, sodium bisulfite and sodium metabisulfite.
5. A shear-resistant, high-drag-reducing, medium-viscosity, slippery water drag reducer as claimed in claim 1, characterized in that: The water-soluble azo initiator is one of 2,2-azo(2-(2-imidazoline-2-yl)propane) dihydrochloride, 2,2-azo(2-methyl-N-(2-hydroxyethyl)acrylamide), and 2,2-azobis(2-methylpropane) hydrochloride.
6. A shear-resistant, high-drag-reducing, medium-viscosity, slippery water drag reducer as claimed in claim 1, characterized in that: The composite initiator is tert-butyl hydroperoxide, ammonium persulfate, sodium bisulfite, and 2,2-azo(2-(2-imidazoline-2-yl)propane) dihydrochloride.
7. A shear-resistant, high-drag-reducing, medium-viscosity, slippery water drag reducer as claimed in claim 1, characterized in that: The preparation method of the sulfonate ion-containing hydrophobic monomer is as follows: Step S1: in a three-necked flask equipped with a magnetic stirrer, a reflux cold flow tube, a thermometer, and two constant pressure dropping funnels, tetradecylamine or hexadecylamine and a catalyst are added in sequence, 2-sodium bromoethylsulfonate or 2-sodium chloroethylsulfonate solution is added to one of the constant pressure dropping funnels, and NaOH solution is added to the other constant pressure dropping funnel; by adjusting the dropping speed of the NaOH solution, the pH value of the reaction is controlled, and the reaction is carried out at a temperature of 50-70° C. for 6-9 hours; after the reaction is completed, a precipitate is precipitated in ethanol, and filtered to obtain an intermediate sodium 2-tetradecylaminoethanesulfonate or sodium 2-hexadecylaminoethanesulfonate; Step S2: dissolving the intermediate obtained in step S1 in dichloromethane, and adding Na2CO3 as an acid binding agent; dropping acryloyl chloride from a constant pressure dropping funnel, controlling the temperature at 15-20°C, reacting for 18-24 hours, removing dichloromethane by reduced pressure distillation, and then recrystallizing with ethanol to obtain the target monomer, which is a sulfonate ion-containing hydrophobic monomer.
8. A shear-resistant, high-drag-reducing, medium-viscosity, slippery water drag reducer as claimed in claim 7, characterized in that: In the step S1, the molar ratio of tetradecylamine or hexadecylamine to sodium 2-bromoethylsulfonate or sodium 2-chloroethylsulfonate is 1:0.8-1:0.9; the catalyst is tetrabutylammonium bromide, and its content is 1% of the mass of tetradecylamine or hexadecylamine; during the reaction, the dropping speed of the NaOH solution is adjusted according to the pH change to control the pH value at 9-12; in the step S2, the molar ratio of the intermediate, Na2CO3, and acryloyl chloride is 1:3:
3.
9. The method for preparing a shear-resistant, high-drag-reducing, medium-viscosity and slippery water drag reducer according to any one of claims 1 to 8, characterized in that: The preparation method is: The acrylamide monomer and the sulfonate ion-containing hydrophobic monomer are added according to the formula ratio, and ultrapure water is used to prepare a mixed solution with a total monomer mass concentration of 20-35%; the hydrophobic unit microblock regulator and the molecular weight regulator are added to the mixed solution, and then the pH value of the solution is adjusted to 7.0-9.0, and the system temperature is lowered to 0-5°C and then a water-soluble azo initiator and a reducing agent are added; nitrogen is introduced and stirred for 30-40 minutes, and then an oxidant is added, and adiabatic polymerization is carried out for 3-8 hours. After the adiabatic polymerization is completed, granulation, hydrolysis, drying, and crushing are carried out to obtain a target polymer.
10. The preparation method as claimed in claim 9, characterized in that The pH value of the solution is adjusted by sodium hydroxide and acetic acid; the pH value of the solution is 8.0-8.5; the temperature of the system is 0° C.; and the thermal insulation polymerization time is 5-7 hours.
Citation Information
Patent Citations
Amphipathic polymerizable monomer and amphipathic tackifying copolymer and preparation method and application thereof
CN102452964A
Hydrophobic associated polymer and preparation method thereof
CN105646771A
Efficient foam scrubbing drag reducing system for natural gas exploitation
CN105924574A
Self-degradable fracturing fluid thickening agent and preparation method thereof
CN115353870A
Shearing-resistant high-drag-reduction high-viscosity slickwater drag reducer and preparation method thereof
CN119241765A
Cited By
Relative permeability improver capable of efficiently controlling water and increasing oil and preparation method of relative permeability improver
CN120271749A
A high-efficiency water-controlling and oil-increasing relative permeability improver and its preparation method
CN120271749B